Electrochemistry of molecules in nanotubes - Mcsweeney, Robert (2016)
The work presented in this thesis describes the use of carbon nanotubes as both electrodes and containers for electrochemical reactions. The cyclic voltammetry (CV) and coulometry of metallocenes, half-sandwich complexes, fullerene containing molecules and organic molecules are presented. The nanoscale confinement in carbon nanotubes affects both the spatial confinement and the electronic properties of the guest-molecule. Encapsulation of molecules can also lead to a change in the electronic properties of the host-nanotube. The specific nature of the interactions between the guest-molecule and nanotube was investigated by the encapsulation of molecules inside carbon nanotubes followed by measurements of the electrochemical redox processes of the guest-molecules using CV and coulometry. The internal diameter of the single-walled carbon nanotubes (SWNT) used throughout this thesis is commensurate with the size of single molecules, which leads to the mechanism of reactions being influenced by the limited space around the guest-molecule. This can also lead to the products of some electrochemical reactions being templated by the nanotube’s shape and size. Furthermore, the unique electronic band structure of carbon nanotubes affects interactions of certain guest-molecules with the internal wall of the nanotube, the magnitude and type of interaction associated with different guest-molecules depends on the energy of the highest occupied molecular orbital (HOMO) of the guest-molecule as well as the electronic states and the Fermi level of the host-nanotube. The effect of this interaction on both the guest-molecule and host-nanotube is determined using CV, coulometry and linear sweep voltammetry (LSV). An example of this is the encapsulation of cobaltocene and ferrocene in SWNT, a strong interaction between cobaltocene (Co(Cp)2) and the nanotube is observed, but only a weak interaction is observed between ferrocene (Fe(Cp)2) and the nanotube through changes in the cyclic voltammetry (CV) of the encapsulated molecules. Additionally, these interactions affect the electronic bands of the nanotube due to the injection of electrons into the nanotube conduction band. Using coulometry and LSV, the magnitude of this charge injection into the nanotube and whether the nanotube will be metallic or semiconducting is determined. The redox processes of the electrochemically induced ligand exchange of CpMeMn(CO)3 inside single-walled carbon nanotubes is probed, investigating how a reaction that relies on both an external nucleophile and the elimination of a ligand is changed when confined in the nanoscale channel of the nanotube. Finally, the use of nanotubes as a reaction vessel for an internal electrochemical reaction is investigated, whereby the nanotubes pre-arrange the reactant molecule in position for particular reactions. The confinement enables an electrochemical reaction that wouldn’t occur in bulk solution and the carbon nanotube templates a new product inaccessible by other means. The electronic and steric interactions of nanotubes with guest-molecules change the properties of the host and the guest, thus leading to exciting new materials and new products that cannot be synthesised otherwise. The results presented in this thesis demonstrate the significance of the electrochemistry of molecules in nanotubes for fundamental chemistry and provide a new methodology of making novel products by utilising carbon nanotubes as reaction vessels and nanoscale electrodes.